Hadith #2337 - Sunan Abi Dawud - Aabad bin al-Wam bin عباد بن العوام; Sa'd bin Tariq, Abu Malik سعد بن طارق بن أشيم أبو مالك الأشجعي; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي (Sunan Abi Dawud)
AbdulAziz ibn Muhammad said: Abbad ibn Kathir came to Medina and went to the assembly of al-Ala’. He caught hold of his hand and made him stand and said: O Allah, he narrates a tradition from his father on the authority of AbuHurayrah who reported the Messenger of Allah (ﷺ) as saying: When the middle of Sha’ban comes, do not fast. Al-Ala’ said: O Allah, my father narrated this tradition on the authority of AbuHurayrah from the Prophet (ﷺ)
Grade: Sahih

Hadith #4945 - Sunan Abi Dawud - Hudhayfah ibn al-Yaman; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Raba'i bin Harash bin Jahsh ربعي بن حراش; Sa'd bin Tariq, Abu Malik سعد بن طارق بن أشيم أبو مالك الأشجعي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I swore allegiance to the Messenger of Allah (ﷺ) promising to hear and obey, and behave sincerely towards every Muslim. AbuZur’ah said: Whenever he sold and bought anything, he would say: What we took from you is dearer to us than what we gave you. So choose (as you like).
Grade: Sahih

Hadith #5081 - Sunan Abi Dawud - Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Sa'd bin Tariq, Abu Malik سعد بن طارق بن أشيم أبو مالك الأشجعي (Sunan Abi Dawud)
if anyone says seven times morning and evening; “Allah sufficeth me: there is no god but He; on him is my trust- he, the Lord of the Throne (of glory) Supreme”, Allah will be sufficient for him against anything which grieves him, whether he is true or false in (repeating) them.
Grade: Hasan

Hadith #5144 - Sunan Abi Dawud - ibn Abbas; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sa'd bin Tariq, Abu Malik سعد بن طارق بن أشيم أبو مالك الأشجعي; Uthman bin Muhammad (Sunan Abi Dawud)
I saw the Prophet (ﷺ) distributing flesh at Ji’irranah, and I was a boy in those days bearing the bone of the camel, and when a woman who came forward approach the Prophet (ﷺ), he spread out his cloak for her, and she sat on it. I asked: Who is she? The people said: She is his foster-mother.
Grade: Da'if